Sistem Pakar Untuk Mendiagnosa Penyakit Bronkho Pneumonia Menggunakan Metode Certainty Factor Pada Klinik Assifa Bengkulu - Shintia Cantika; Indra Kanedi; Juju Jumadi (UNIVED Press, 2023)
Abstract_Broncho pneumonia can occur at any age caused by pneumococcal bacteria. Usually the symptoms of bacterial pneumonia are preceded by a mild respiratory infection a week earlier. Implementation of expert systems in the field of health and medicine in the form of initial diagnosis, treatment of the results of the diagnosis, determination of visible clinical symptoms. As-Shifa Bengkulu Clinic is one of the health clinics in the city of Bengkulu. In its service, this clinic serves all those related to disease from children to adults. One of them is Broncho Pneumonia. The lack of expert doctors in handling every problem in this clinic is one of the problems that occur. So that this can cause patients to wait a long time or not be able to consult directly with a doctor. Of course this takes time and will be in vain if the doctor concerned is not available. Therefore an expert system is designed to diagnose Broncho Pneumonia with the Certainty Factor method. This expert system is designed using the PHP Programming Language and MySQL database. The expert system created can make it easy for users to consult online about Broncho Pneumonia.